Penguatan Kompetensi Pedagogik Calon Guru melalui Inovasi Prototipe Pembelajaran Merdeka Belajar: Praktik Magang di Kampus Guru Cikal - Nurul Farhin (BADAN PENERBIT STIEPARI PRESS, 2025)
The Cikal Teacher Campus internship program is a vehicle for strengthening students' pedagogical competence through innovative learning based on the principles of Merdeka Belajar. This activity was carried out for 21 weeks at SMA Plus Teknologi Sukabumi with a design thinking approach and a self-directed learning model. The purpose of this activity is to create collaborative learning innovations across subjects that answer real problems in the classroom. The activity method uses a participatory approach through observation, teaching assistance, prototype preparation, and classroom trials. The results of the community service show an increase in student participation, understanding of cross-disciplinary materials, and entrepreneurial skills based on local potential. This activity shows that a contextual, collaborative, and student-centered learning approach can increase the effectiveness of learning and the relevance of education at the secondary school level.